EP.FRI.511 Optimising Ambulatory Ultrasound in Emergency Surgery. (28th October 2021) - Handa, Ishita; Pearson, Katherine; Day, Anne Marie; Kirkby-Bott, James; Berry, David
Abstract: Aims: Service provision and assessing the impact of future innovations can best be assessed by accurate reproducible data collection. The traditional model for our ambulatory surgical clinic with ultrasound allowed booking directly from the Emergency Department (ED) without discussion with the Surgical Team. We questioned whether this was the correct model and changed to a model of discussion with the Surgical team before booking in an effort to better utilise resource and reduce unnecessary footfall in the hospital. Methods: We reviewed the outcome data of consecutive ambulatory ultrasound clinic referrals before and after implementation of this change in practice (1 month before and after the change) Results: Ninety four ambulatory Ultrasound referrals were reviewed. In the first cohort 30 of 50 patients came directly from ED without discussion. A positive USS report was recorded in 8 of the 30 (27% USS positivity rate). After the change in practice to discuss with the surgical team, 11 of 43 patients originated primarily from ED with a positive finding in 4 patients (36%). Conclusions: A key aim of service improvement is to optimise / improve utilisation of resource. This must be achieved without missing pathology. In this study we reduced the number of scans performed by ED whilst increasing the likelihood of a positive scan. This change in practice better utilised resource and reduced unnecessary footfall in the hospital.